Potability of borehole, bottled and municipal water in Harare - Kativhu, Christabel Chenai (Midlands State University, 2014)
Human health depends on reliable access to safe drinking water, but in many developing countries there are problems of accessing it. This is mainly attributed to water pollution, poor infrastructure for potable water treatment and unhygienic practices in water bottling companies. This study was carried out to assess the physico-chemical and microbiological quality of borehole, bottled and municipal water in Harare (Zimbabwe), by evaluating the compliance of each water type with WHO standards. The study period was from February 2012 to May 2012. Water samples were collected from five boreholes in different high density suburbs, five different brands of bottled water and municipal water. A total of 180 samples were collected and each was analysed for 17 parameters. Standard Operation Procedures (SOPs) at EMA laboratory were followed for analysis of these parameters. All the bottled water brands and municipal water tested negative for all faecal coliforms. All chemical parameters in bottled and municipal water complied with WHO standards. Heterotrophic bacteria were within WHO standards (100 colonies/ 100 ml) in municipal water and in all bottled water brands except for brands B and C. The occurrence of heterotrophic bacteria in some bottled water brands exposes consumers to gastrointestinal diseases. All microbiological parameters complied with WHO standards in boreholes A and B. However pH, manganese and nitrates did not comply with WHO standards in boreholes A and B. Faecal coliforms were detected in boreholes D and E. The concentration of heavy metals in boreholes C, D and E did not comply with WHO standards. High concentration of heavy metals predisposes consumers to health problems such as bioaccumulation of heavy metals. Borehole E had the highest TDS (1180.83 mg l-1) which did not comply with WHO standards. Overall, each borehole in Harare failed to comply with WHO standards for most parameters. The results suggest that the safest water to drink in Harare is municipal water because it showed consistent compliance with WHO standards in all tested parameters. For bottled water not all brands are safe (3 out of 5 complied). Brand E (carbonated water) proved to be the safest among other brands as no bacteria were detected.